Not in education, employment and training status in the early stages of bipolar I disorder with psychotic features. Issue 6 (27th July 2021) - Cotton, Sue M.; Filia, Kate M.; Lambert, Martin; Berk, Michael; Ratheesh, Aswin; Schimmelmann, Benno G.; Macneil, Craig; Hasty, Melissa; McGorry, Patrick D.; Conus, Philippe
Abstract: Objective: There is a lack of existing research regarding young people with bipolar I disorder (BD‐I) and psychotic features, who are not in education, employment, and training (NEET). Thus, the aims of the study were to: (a) establish rates of NEET at service entry to a specialist early intervention service; (b) delineate premorbid and current variables associated with NEET status at service entry and (c) examine correlates of NEET status at discharge. Method: Medical file audit methodology was utilized to collect information on 118 patients with first episode psychotic mania treated at the Early Psychosis Prevention and Intervention Centre (EPPIC), Melbourne, Australia. NEET status was determined using the modified vocation status index (MVCI). Bivariate and multivariable logistic variables were used to examine relationships between premorbid, service entry and treatment variables, and NEET status at service entry and discharge. Results: The NEET rate was 33.9% at service entry, and 39.2% at discharge. Variables associated with NEET status at service entry were premorbid functioning and polysubstance use. NEET status at service entry was the only significant correlate of NEET status at discharge. When service entry NEET was taken out of the model, substance use during treatment was predictive of NEET status at discharge. Conclusions: NEET status at service entry was related to a history of premorbid decline, and risk factors such as substance use and forensic issues. NEET status can decline during treatment, and utility of vocational intervention programs specifically for BD, in addition to specialist early intervention, needs to be examined.